Do agri-environment measures help improve environmental and economic efficiency? Evidence from Bavarian dairy farmers - Ait Sidhoum, Amer; Mennig, Philipp; Sauer, Johannes (Oxford University Press (OUP), 2023)
This study presents an innovative empirical application to the assessment of agri-environment measures on environmental and economic efficiency. Using a multi-equation representation with desirable technology and its accompanying undesirable by-production technology, we investigate the effects of agri-environment measures on farm-level environmental and economic efficiency. A combination of propensity score matching and a difference-in-difference approach is used to estimate the policy effect. The application focuses on a balanced sample of Bavarian dairy farms surveyed between 2013 and 2018. Results suggest that agri-environment schemes do not alter farms’ economic efficiency, whereas environmental efficiency does not seem to be stimulated by schemes participation.
Keywords: agri-environment schemes; policy evaluation; nitrogen pollution; environmental performance; data envelopment analysis